Твердофазный экстрагент на основе кремнезема, модифицированного солью арилдиазония, для извлечения фенола - Зайцев, В.Н.; Халаф, В.А.; Зайцева, Г.Н. (Украинский химический журнал, 2006)
Розроблено схему одержання нового твердофазного екстрагенту (ТЕ) на основі кремнезему для селективного вилучення фенолу з води. Селективність дії ТЕ базується на утворенні азосполуки між фенолом і ковалентно-закріпленої на поверхні SiO₂ солі арилдіазонію. Встановлено оптимальні умови вилучення фенолу в варіанті динамічного сорбційного концентрування. Повне вилучення фенолу з води досягається в інтервалі рН 7—10 і швидкості пропускання 0.5 см³/хв. При цьому коефіцієнти розподілу досягають 1×10⁴ мл/г, а ємність до проскоку фенолу — 0.376 мг/г. The scheme of a new solid phase extractant (SPhE) preparation scheme on the silica bases was developed for selective extraction of phenol from water. The selectivity of SPhE action is based on the formation of azocompound between phenol and covalently bonded groups of aryldiazonium salt on the silica surface. The optimum conditions of phenol extraction in the mode of dynamic sorption concentration were determined. It’s shown that the complete extraction of phenol from water reaches in the range of рН 7—10 and the flow rate 0.5 см³×min–1. Thus the distribution coefficients of phenol become 1×10⁴ ml/g, and capacity till phenol breakthrough — 0.376 mg/g.